A multicultural approach to teach sustainability - Nídia Sá Caetano; João Simões Rocha; José Carlos Quadrado; José Marílio Cardoso; Manuel Carlos Felgueiras (OmniaScience, 2016)
Globalization is a tendency that covers all society perspectives in general, and the high education in particular. The main traditional objective of these institutions was to prepare domestic students with a set of skills. The research competition and universities rankings, as well as the need to reach other publics pushed them towards internationalization. The exchange of students across the UE is a well-known reality which success is largely due to cultural similarities. However, a set of issues raises in importance when students from different cultures are involved. We proposed an International Summer Course with a layout specifically designed to identify those questions. In our experience the class included Korean and Portuguese students in the same proportions to develop some work under the framework of sustainability, a specific theme chosen in order to foster consensus. Aiming at a higher level of internationalization and having in mind that students could gain from an intensive and multicultural experience ISEP organized its first Engineering for Sustainable Development (E4SD) Summer Course, in July 2014. This work reports some results from this experience, which included a Problem Based Learning (PBL) approach, and points new directions. In fact, PBL seemed to be a way of promoting integration and the inclusion of multiple cultures allowed the analysis of different perspectives which otherwise would not have been considered. On the other hand, all the students had an international experience, in a non native language, which has driven them out of their confort zone.